Redefining literacy for the 21st century - Warlick, David; Gale Group (Worthington, Ohio Linworth Pub., 2004)
A new definition of literacy for the Information Age that can be passed on to learners of all ages. Find suggestions and resources for discovering your own path to promoting literacy in the 21st century.
Introduction and user's guide -- Setting the stage-a future fiction -- Exposing the information -- Employing the information -- Expressing ideas compellingly -- Ethics and context -- Conclusion! A student of the future.
Electronic reproduction.
Keywords: Computers and literacy; Education -- Effect of technological innovations on; Curriculum planning; Electronic books